Hypothalamic Hamartomas and Gelastic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Stanford University and other neurological centers in the United States performed a retrospective review and analysis of the clinical presentation and neuroanatomical features of hypothalamic lesions in 100 cases of gelastic epilepsy.